Connectivity Patterns for Direct Developing Invertebrates in Fragmented Marine Habitats: Fish Farms Fouling as Source Population in the Establishment and Maintenance of Local Metapopulations - Victoria Fernandez-Gonzalez (Frontiers Media S.A., 2021)
Artificial structures can be considered as high spatially structured habitats in the marine pelagic system, where patch connectivity would be strongly dependent on the exchange of larvae or dispersing individuals. Fish-farms located offshore may alter ecological connectivity, modifying trophic resources, and species dispersal among patches. High population densities of invertebrates can be found associated with fish-farm fouling communities, which can act as a seed source, contributing to the patterns of connectivity through individuals exchange between subpopulations or with sink populations. A field experiment was performed to analyse the role of fish-farms in the colonisation of new uninhabited habitats (floating experimental units) located at different positions relative to the fish farm and the main current, containing artificial habitats with and without feed pellets similar to those used in the fish farm. Amphipods were used as example of direct developing invertebrates for studying dispersing individuals from the fish farm to the new habitats. The richest and most abundant populations in this study were found close to and downstream of the fish farm, surpassing 1,000 amphipods at their maximum. Moreover, some floating habitats located more than 2 km from the fish farm were colonised in only 15 days. Thus, the role of fish farms has been shown to extend beyond a ‘stepping-stones’ effect in species dispersal, and have an additional effect on ecological connectivity by increasing population sizes and acting as population source. Our study aims to provide recommendations for coastal zone management in order to predict potential spread from fish farms to other platforms in the future and promote solutions related to interactions and consequences of connectivity within and between marine facilities.